Infrared Survey of Giant M Stars - Bambang Hidajat (Journal of Mathematical and Fundamental Sciences, 1969)
Abstract. A spectrocospic survey in an area of 5 squares degrees, located in the general direction of the Palomar-Groningen Variable-Star Field 2 , yields 263 Giant M stars. A test of completeness shows than the survey was complete down visual magnitude 16 for early giant M stars and to visual magnitude 17 for late giant M stars. The space density distribution of the stars is presented.Ichtisar. Survey setjara spektroskopis bintang raksasa M, didaerah seluas 5 deradjat persegi, kearah Palomar-Groningen Variable-Star Field no. 2, menghasilkan 263 bintang2 raksasa kelas M. Sebuah test statistic menundjukkan bahwa survey tersebut lengkap sampai magnitude 16, untuk bintang M-azeal, dan sampai magnitude 17, untung bintang2 M-tua. Distribusi bintang2 tersebut didalam ruang djuga dihitung dan dibitjarakan.